Interprofessional undergraduate breastfeeding education: A scoping review protocol [version 1; peer review: 2 approved, 1 approved with reservations] - Elaine Lehane; Aoife Long; Edina Hanley; Liz Cogan; Siobhan Ward; Helen Mulcahy; Margaret Murphy; Patricia Leahy-Warren; Aoife Fleming (HRB Open Research)
Objective To review and summarise interprofessional breastfeeding curricula—educational initiatives involving multiple health professions—that have been proposed for undergraduate or pre-registration health students. This review will help guide the development of future Interprofessional Education (IPE) curricula for undergraduate health students, specifically in the area of breastfeeding care. Introduction Breastfeeding care and support from healthcare professionals are vital for breastfeeding success. To ensure mothers receive high-quality, consistent care, healthcare professionals must receive comprehensive, evidence-based breastfeeding education. However, there is limited understanding of how breastfeeding curricula are delivered across different disciplines in undergraduate health programs, particularly in the context of IPE. Inclusion criteria Primary research designs, including quantitative, qualitative and mixed-method studies and evidence syntheses of primary research including systematic and scoping reviews that meet the inclusion criteria will be considered. Position papers and policy documents will also be considered for inclusion in this scoping review. Methods Medline (Ovid), CINAHL (EBSCO), ERIC (EBSCO), Social Sciences, and Cochrane Databases of Systematic Reviews will be searched with English language and date restrictions (2005-current). Titles and abstracts and full-text articles will be independently screened by two reviewers. The reference lists of the included studies will be searched. A grey literature search will be undertaken on Google scholar, BASE and National Institute for Health and Care Excellence (NICE) website in October 2024. Studies will be screened in Covidence by two independent reviewers. All reviewers will agree on the included studies. Data will be extracted and presented graphically using figures and tables. Narrative summary text will accompany the tables and figures.